Pragmatics, discourse and philosophy (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
Following the linguistic turn in analytical philosophy, concern for language underlies some of the most important strands of philosophical practice, making issues of mind, language and discourse virtually inseparable elements of scientific inquiry. Just as philosophy looks to language and linguistics to endorse different ontological and epistemological postulates, linguistics looks to philosophy in addressing its key questions of meaning, function and use. In this paper I argue that pragmatics and discourse analysis are areas where the relation between language, linguistics and philosophy is particularly salient. Crucially, philosophy, its conceptions and frameworks, should never be viewed as ‘external’ to discourse. Rather, discourse and discourse study involving pragmatic tools are, in themselves, areas of intense philosophical practice. Results of this practice are relevant and of interest to not only language philosophers, but also to those exploring ontological and epistemological matters of general philosophy.